Exploring performance-oriented analysis through an examination of title character's two arias in Carlisle Floyd's "Susannah" - Cole, Shannon (University of Ottawa (Canada), 2008)
This thesis adapts a model of performance-based analysis and utilizes it to interpret the title role in Carlisle Floyd's opera, Susannah (1955). Using John Rink's model as a guide, this performance-oriented analysis reveals the relationships between the musical and textual elements within the role, and allows the performer to prioritize which relationships will most strongly guide her interpretation. The first chapter introduces the opera's libretto and its literary origins, outlines the analytical methodology, and addresses pertinent literature in the field of performance analysis as well as that regarding the opera Susannah. The second chapter provides the historical and political context of the opera, including discussion of Floyd's contemporaries and the impact of McCarthyism in 1950s America. The third and fourth chapters present analyses of Susannah's two arias, "Ain't It A Pretty Night" and "The Trees On The Mountains" respectively. The theoretically-based findings are weighed against actual performance considerations to create an analysis that could feasibly inform a performance. The fifth chapter situates the two arias in the context of the opera, and points to further research possibilities.
Keywords: Music.; Theater.